The Role of Mosque Youth in the Prosperity of the Al-Falah Mosque - Rizka Amalia; Azlia Fasya Kintara; Nurul Aulia; Fauzul Azmi Purba; Arlina, Arlina (al-Afkar, Journal For Islamic Studies, 2025)
The aim of this research is to describe the role of Al-Falah mosque youth in making the mosque prosperous (case study of Al-Falah mosque youth management) and to determine the role of Al-Falah mosque youth in making the mosque prosperous. Even though the management of this mosque is not fully managed by the mosque's youth, there are still many teenagers who are involved in congregational prayers because the chairman of the mosque's youth requires each member of the mosque's youth to attend congregational prayers for at least 3 prayer times, but if anyone is unable to do so Congregational prayer can be condoned for certain reasons. There are also many routine activities carried out by mosque youth such as weekly Koran reading, sports activities and other activities. This research uses a qualitative descriptive method, namely an interview method that describes events according to actual circumstances. As a result of this research, we found that they were quite good at implementing activity programs, and they played an active role in caring for the mosque's environment. The role of mosque teenagers in the prosperity of the Al-Falah mosque is quite good in the involvement of teenagers in the management of activities carried out by the mosque.